Repurposing losartan potassium against rheumatoid arthritis via transdermally-delivered leciplexes: Accentuated efficacy through modulation of angiotensin II/AT1R/AT2R axis - Amira A. Hussein; Basmah N. Aldosari; Randa M. Zaki; Obaid Afzal; Adel A. Ali; Heba M. Aboud; Yasmin M. Ahmed; Demiana M. Naguib (International Journal of Pharmaceutics: X, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory ailment which preferentially impacts the synovial membranes of joints and ultimately triggers cartilage and bone erosion. Angiotensin II (Ang II) participates in the pathogenesis of RA; hence, Ang II receptor blockade, accomplished through a specific inhibitor such as losartan potassium (LST), may confer an effective therapeutic avenue for RA. This study aimed to develop, optimize, and characterize LST-loaded leciplexes (LST-LPXs) to ameliorate its bioavailability and prolong its therapeutic efficacy for combating RA. To accomplish this objective, LST-LPX dispersions were assembled through a single-step process and optimized via D-optimal design for various physicochemical traits employing Design-Expert® software. Also, pharmacokinetic studies were explored in rats. Additionally, in complete Freund's adjuvant-induced RA in Wistar rats, RF, COMP, NADPH oxidase, NO, IL-6, TNF-α, besides Ang II and its receptors (AT1R & AT2R) were measured. The optimum LST-LPXs formulation elicited acceptable entrapment efficiency (88.05%), nano-scaled spherical morphology (246.71 nm), controlled release over 24 h (86.33%), and adequate permeation properties through the skin (417.83 μg/cm2). The pharmacokinetic analysis disclosed a snowballed bioavailability of the optimized LST-LPXs gel by 3.08- and 1.2-fold versus the oral solution and crude gel, respectively. The optimum LST-LPXs gel divulged accentuated anti-arthritic effects, evidenced by significant suppression of rheumatoid, oxidative stress, and inflammatory biomarkers coupled with corrections of AT1R and AT2R protein expression. Practically, the current findings proposed a compelling proof-of-principle that the transdermal LST-LPXs could serve as a non-invasive promising nanoparadigm for RA tackling.